A qualitative study of organizational and psychosocial factors in the burnout of italian correctional officers - Rania, Nadia (The prison journal, 2020)
Correctional officers (COs) are subject to the development of burnout syndrome. This investigation focuses on those factors that contribute to burnout syndrome in COs who work in Italian penitentiary institutions. Utilizing a qualitative methodology with 50 northern Italian COs, the study finds burnout to be caused by two types of factors, organizational and psychosocial. Notably, the results highlight feelings of anguish, sadness, and abandonment and CO requests for psychological help.